Improvement of non‐invasive markers of NAFLD from an individualised, web‐based exercise program. Issue 8 (25th July 2019) - Huber, Yvonne; Pfirrmann, Daniel; Gebhardt, Ines; Labenz, Christian; Gehrke, Nadine; Straub, Beate K.; Ruckes, Christian; Bantel, Heike; Belda, Eugenio; Clément, Karine; Leeming, Diana J.; Karsdal, Morten A.; et al.
Summary: Background: Lifestyle modifications remain the cornerstone of treatment in non‐alcoholic fatty liver disease (NAFLD). However, they requently fail related to the inability of patients to implement lasting changes. Aims: To evaluate the effects of a short, web‐based, individualised exercise program on non‐invasive markers of hepatic steatosis, inflammation and fibrosis. Methods: Patients with histologically confirmed NAFLD underwent an 8‐week, web‐based, individualised exercise program that contained bidirectional feedback. Results: Forty‐four patients entered the study and 41 completed the assigned training goal (93.2%). In the completer population, 8 weeks of individualised exercise increased the VO2peak by 12.2% compared to baseline ( P < .001). ALT and AST decreased by 14.3% ( P = .002) and 18.2% ( P < .001) and remained at this level until follow‐up 12 weeks after the intervention. Markers of inflammation including hsCRP, ferritin, and M30 decreased. In parallel, gut microbiota exhibited increased metagenomic richness ( P < .05) and at the taxonomic levels Bacteroidetes and Euryarchaeota increased whereas Actinobacteria phylum decreased. Surrogate scores of steatosis and fibrosis including the fatty liver index (FLI), FiB‐4, APRI and transient elastography showed significant reductions. In parallel, a marker of procollagen‐3 turnover (PRO‐C3) decreased while C4M2, reflecting type IV collagen, degradation increased suggesting beneficial hepatic fibrosis remodelling from exercise. Also, an enhancement in health‐related quality of life was reported. Conclusion: The current study underlines the plausibility and potential of an 8 week individualised web‐based exercise program in NAFLD. Clinical trial number: NCT02526732